Ce qui change avec le temps (grammatical)… Substitution passé composé / imparfait et imparfait / passé composé dans les phrases plurielles en français - Sikora, Dorota; Sypnicki, Józef (Neophilologica, 2010)
The goal is that our article is not accountable or even less, to take sides in the debate on substation PC / IMP and IMP / PC. Quite the contrary, we are proposing to clarify some issues related to the substitution of temporal operators in the descriptions of multiple events, we will search in the current work tracks and tools for our investigation. Throughout this paper, we try to show the elements for the replacement PC / IMP and IMP / PC in sentences referring to many. It is, indeed, they are from different levels of analysis, although strictly interrelated.